0757 Association Of Sleep And Technologies In A Sample Of Italian Adolescents. (12th April 2019) - Castronovo, Vincenza; Marelli, Sara; Nosetti, Luana; Lonati, Irene; Agosti, Massimo; Broggi, Giacomo; Castelnuovo, Alessandra; Fossati, Andrea; Somma, Antonella; Ferini-Strambi, Luigi
Abstract: Introduction: In the last years more clinical and academic attention has been demonstrated to sleep deprivation in adolescents because of the derived risk of physical and mental problems. One of the main reason that keep adolescents in a persistent sleep deprivation status is the increased use of technologies that seem to influence the regular release of melatonin and to stimulate the wake network functioning. Aim of our study was to assess the relationship between pre-sleep habits and subjective sleep duration and quality during weekdays (WD) and weekend (WE) in a sample of Italian adolescents. Methods: 972 adolescents aged 13-20 filled a self-administered questionnaires that included information on pre-sleep habits (such as browse the internet, watch TV, listen to music, use the smartphone, etc, ..) and on subjective sleep (total sleep time [TST], bet time [BT], wake-up time [WU], sleep latency [SL]). Results: Mean age was 15.7 (SD 1.4) yrs, 59% were female. Mean TST during WD was 456.1 (SD 57.8) min., and 551.3 (SD 87.1) min. during WE. Mean BT was 23.3 (SD⋯..) with no significant difference between WD and WE. WU time was at 06:40 a.m. (SD) during WD and at 09:50 a.m. during WE. Significant correlations between subjectively reported sleep and pre-sleep habits were found (p<.005). In particular those adolescents going to sleep later and with a lower TST during WD were the ones with the higher use of the internet, smartphone and videogames. Moreover, also on the WE, a significant correlation between late BT and increased SL was found with the following pre-sleep habits: browse the internet, listen to music, smartphone use, watch movies. Conclusion: Our results confirm other literature data that show the negative impact of technologies on sleep. In particular in our sample browse the internet, listening to music, smartphone use and videogames use postponed BT and reduced WD sleep duration. These findings underline the negative impact of technologies on sleep in adolescents and open a possible way of improving pre-sleep habits by means of educational and sleep hygiene strategies. Support (If Any): none